2020
DOI: 10.21608/ejchem.2020.22727.2352
|View full text |Cite
|
Sign up to set email alerts
|

Economic polymer-based waterproofing membranes by incorporation of wastes to form eco-friendly material

Abstract: Waste recycling is a way to produce innovative low cost eco-friendly materials to solve environmental problems caused by different types of industrial by-product and polymeric wastes. Natural rubber loaded with different types of waste materials Calcium Hydroxide Ca(OH)2, Calcium Carbonate (CaCO3), Fly Ash (class F) and Waste rubber (WR) by mixing through open mill and then pressed in hot press to obtain low cost eco-friendly waterproofing membranes with desired properties. All samples pass the water penetrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…From the above figure we can see that water absorption present decreases as the concentration of the foaming agent increases this may be due to the formation of closed pores in the matrix (illustrated in the microstructure analysis). It is clear from the above results that all samples lies in the range of water insulating materials, this considered a promising results for foamed rubber [26,38].…”
Section: 3water Absorptionmentioning
confidence: 53%
See 2 more Smart Citations
“…From the above figure we can see that water absorption present decreases as the concentration of the foaming agent increases this may be due to the formation of closed pores in the matrix (illustrated in the microstructure analysis). It is clear from the above results that all samples lies in the range of water insulating materials, this considered a promising results for foamed rubber [26,38].…”
Section: 3water Absorptionmentioning
confidence: 53%
“…Vulcanization of the rubber compounds was carried out in an electrically heated uniaxial press between stainless steel plates at 150 o C and pressure 150 bar for a dwell time of 45 min. Samples were prepared by different shapes of molding according to the measurement types [26] Thermal Conductivity test conducted using KD2 -Pro portable thermal conductivity meter according to transient method techniques. Cubic samples of side length 5 cm at different temperature were used according to the standard .Each sample was cured for 24 hours at each temperature and then measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Waste CaCO3 were collected from a factory byproduct. The samples used to perform experimental tests were prepared with the recipe presented in Tables 1 and 2, The vulcanization of the rubber composites was carried out in a hydraulic press under a pressure of about 150 bar, temperature 150 o C and time of 45min [2].…”
Section: Experimental Workmentioning
confidence: 99%
“…Water absorption test, water tightness, thermal stability, UV weathering, hardness and mechanical measurements were investigated for natural rubber loaded with calcium hydroxide (CaOH), calcium carbonate (CaCO3), waste rubber and fly ash (class F) as industrial by products. The tests results showed that rubber loaded with waste rubber, fly ash and calcium carbonate are suitable for marketing as a waterproofing membranes [2]. An economical construction material may be obtained by natural rubber (NR) clay composite with desirable thermal, mechanical and waterproofing properties.…”
Section: Introductionmentioning
confidence: 99%